„Nowe porządki” z socjalizmem w tle. Szkic do powojennych dziejów Biblioteki Uniwersyteckiej w Poznaniu (1945–1956) - Mania, Elżbieta (Biblioteka Uniwersytecka w Poznaniu, 2017)
Powojenna historia biblioteki Uniwersyteckiej w Poznaniu zapisała się wieloma rozdziałami. Pierwszym był trudny okres usuwania zniszczeń. Drugim – organizowanie i rozwój działalności oddziałów bibliotecznych. Ważnym zadaniem bibliotekarzy było także zabezpieczanie księgozbiorów porzuconych i opuszczonych z terenów Wielkopolski, Ziem Odzyskanych i Śląska. tymczasem, jeszcze zanim usunięto ślady obecności Universitätsbibliothek zorganizowanej w murach poznańskiej biblioteki w czasie okupacji, ówczesna sytuacja polityczna narzuciła nowe – sowieckie wzorce. Odtąd powinnością bibliotekarza, oprócz gromadzenia, opracowywania i udostępniania zbiorów, była walka o postawę ideologiczną czytelnika. Wpływowe władze partyjno-państwowe wprowadziły zatem szereg zarządzeń, by czuwać nad całokształtem działalności bibliotekarstwa polskiego. Praktyki te przybierały różne formy, kreśląc kolejne karty bibliotecznych dziejów. im poświęcony będzie niniejszy artykuł.

The imminent post-war history of the University library in Poznań was written in a number of chapters. the first chapter covers the time of measuring the war damages and rebuilding the existing infrastructure. the second chapter is marked by organization and development of the library’s departments. One of the major tasks to be performed by the librarians was to accommodate abandoned book collections from the Wielkopolska region, the so-called Recovered territories and from Silesia. things as they were, even before the last traits of the German “Universitätsbibliothek”, established during the occupation in Poznań, had been removed, the contemporary political situation dictated and imposed new Soviet-style patterns. it was from then on that the duties of a librarian included, alongside book acquisition, processing and circulation of the collection, an obligation to struggle for ideological stance of the library’s user and reader. appropriately, the omnipresent and omnipotent Communist party and Communist state authorities introduced a number of regulations that were to secure the “proper” and adequate totality of circumstances in the activity of Polish librarianship. these notorious practices took on different forms thus shaping the successive chapters in the history of libraries in Poland and are described and discussed in the present article.
“New order” Communist-style. A contribution to the post-war history of the University Library in Poznań (1945–1956)
Keywords: Biblioteka Uniwersytecka w Poznaniu; książka; historia bibliotekarstwa naukowego; XX wiek; sowietyzacja; Poznań University library; book; history of research librarianship; twentieth century; Sovietization